The endangerment of Mendriq's traditional knowledge in Malaysia. (28th August 2019) - Zal, W.A. Amir; Omar, Mustaffa; Nor, Hasan Mat; Isa, Kamarudzaman Md.
Traditional knowledge is becoming important to the Orang Asli for survival because they live near the forest and are confronted with changes. However, in changing times, the ownership of traditional knowledge has not been getting any attention from the Orang Asli. Moreover, their ownership of such knowledge is given impetus by the insistence on monetary value. Based on these concerns, this article proposes to explore the ownership of traditional knowledge and its endangerment among the Mendriq. The data on Orang Asli was collected from the Mendriq tribe in Kuala Lah, Gua Musang, Kelantan, Malaysia through focus group discussions (FGD) and in-depth interview methods. The study found five states of traditional knowledge ownership among participants. First, knowing the name and the nourishment; second, knowing the name and confusing the function; third, knowing the nourishment but not the name; fourth, knowing the name and not the physical form; and fifth, not knowing the name or the function. Those states happen as a result of three factors, namely, individual, community and traditional knowledge per se. However, this study found that monetary value is a prominent push factor for traditional knowledge ownership. This reality has had positive and negative effects on traditional knowledge. To counter that, capacity-building activities for traditional knowledge should be promoted.